2017
DOI: 10.1159/000471801
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Lower Back Pain: Study Protocol of a Comparative Effectiveness Study on Yoga, Eurythmy Therapy, and Physiotherapeutic Exercises

Abstract: Background: We aim to compare the effectiveness of 3 active interventions, i.e., yoga, eurythmy therapy, and physiotherapeutic exercise, on chronic lower back pain. Methods: In this randomized controlled trial over 16 weeks (8 weeks of intervention, 8 weeks of follow-up), data of individuals with chronic lower back pain will be analyzed. Interventions are implemented as group sessions (75 min) once per week. Participants receive a manual for home-based practice and are assessed before and at the end of the 8-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…For a clear identification of the effects of exercise motions, objective physical variables, such as muscle flexibility, muscle strength, and changes in waist circumference, should be evaluated. Both age groups in our study showed significant differences in disability after lower back exercises, confirming previous reports 19 , 27 of exercises significantly reducing disability in patients with low back pain. The Oswestry Disability Index, which was used in our study, accounts for pain, personal hygiene, object lifting, walking, sitting, standing, sex life, social life, and travel.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For a clear identification of the effects of exercise motions, objective physical variables, such as muscle flexibility, muscle strength, and changes in waist circumference, should be evaluated. Both age groups in our study showed significant differences in disability after lower back exercises, confirming previous reports 19 , 27 of exercises significantly reducing disability in patients with low back pain. The Oswestry Disability Index, which was used in our study, accounts for pain, personal hygiene, object lifting, walking, sitting, standing, sex life, social life, and travel.…”
Section: Discussionsupporting
confidence: 92%
“…This study was conducted to verify the effects of a Web exercise video program for the lower back on the pain, muscle strength, disability, and QOL of middle-aged and older individuals who visited a joint center for chronic low back pain. In this study, when the lower back exercises were performed for 8 weeks, low back pain was significantly relieved in both age groups, thereby supporting previous results 19 21 and indicating that exercise intervention for 8 weeks is effective for low back pain relief. Considering the report 12 that a 4-week program has no effects on pain, we inferred that the effects may manifest in the fourth to eighth weeks of exercise.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…162 Another three-armed RCT of the clinical comparative effectiveness of yoga, eurythmy therapy and physical therapy for chronic low back pain has recently been completed and its published results are pending. 163 Of course, there is much other published literature on anthroposophic medicine that also include several modern, rigorously-documented case reports (using published CARE guidelines) and real-world observational studies pointing to its effectiveness. 57,135,164 Prospective Observational Studies in Support of Anthroposophic Medicine and its Related Therapeutic Recommendations Several prospective observational studies on anthroposophic medical practices document the very low use of antibiotics and can likely contribute to an effective approach to reduce antibiotic use more generally and reduce the problem of antibiotic resistance (selection bias cannot be completely ruled out).…”
Section: Effectiveness Of Anthroposophic Medicine-overviewmentioning
confidence: 99%
“…Eurythmy therapy has specific effects in healthy subjects, such as reducing fatigue [33] and stress [40,41]. Moreover, studies describe a reduction of a range of symptoms [42][43][44][45][46][47][48], as well as improvements in quality of life [40,48] in patients with various chronic diseases and in different target groups (i.e., children, adolescents, adults) [49,50]. As observed with other mind-body therapies [51][52][53][54][55], improvements have also been described in heart rate variability (HRV) parameters (i.e., parameters that measure the adaptability of the autonomic nervous system), as well as in circadian patterns of HRV, after eurythmy therapy training [33,[56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%